2017
DOI: 10.1364/oe.25.002594
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor lasers using birefringent filters: experimental demonstration with Cr:Nd:GSGG and Cr:LiSAF

Abstract: Abstract:In this study, we numerically and experimentally investigate application of birefringent filters (BRFs) as frequency selective elements in multicolor lasers. A BRF plate made out of crystalline quartz with an arbitrarily oriented optical axis has been explored. Simulation results have shown that compared to regular BRFs where the optical axis lies in the plane of the plates surface, a BRF with an optical axis pointing out of its surface enables design flexibility in filter parameters, providing access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Moreover, output powers exceeding 100 W was obtained in dual-wavelength operation, which is, to our knowledge, is one of the highest output powers obtained in this regime [59]. It is clear that, with properly designed birefringent tuning elements optimized for multicolor laser operation, cryogenic Yb:YLF gain media could also be used in generating high power multicolor lasing in both cw [59,60] and cw mode-locked [61][62][63] operation regimes. Fig.…”
Section: Investigation Of Wavelength Tuningmentioning
confidence: 75%
“…Moreover, output powers exceeding 100 W was obtained in dual-wavelength operation, which is, to our knowledge, is one of the highest output powers obtained in this regime [59]. It is clear that, with properly designed birefringent tuning elements optimized for multicolor laser operation, cryogenic Yb:YLF gain media could also be used in generating high power multicolor lasing in both cw [59,60] and cw mode-locked [61][62][63] operation regimes. Fig.…”
Section: Investigation Of Wavelength Tuningmentioning
confidence: 75%
“…There exist lasers that directly output multiple laser lines. Both continuous wave and pulsed operations of such lasers have been demonstrated [10,11]. However, the spectral profile of the gain medium and the filters, which are used for line selection, determine the frequency difference between the laser lines.…”
Section: Optical Beats With Beat Frequencies Exhibiting Hz-level Precmentioning
confidence: 99%
“…This is in general very useful, since it enables optimization of performance for different applications. As an example, a recent study demonstrated advantages of off-surface optic axis BRFs in multicolor lasing [9,20].…”
Section: A Effect Of Optic Axis Direction On Free Spectral Rangementioning
confidence: 99%
“…On the other hand, as several earlier studies with quartz birefringent filters has already shown, this particular case is not really optimum for many applications. Compared to regular birefringent filters, BRFs with optic axis pointing out of its surface provides a much broader set of filter parameters (named as diving optic axis birefringent filters or off-surface optic axis birefringent filters in the literature) [1, 3,6,9]. In particular, wisely designed off-surface optic axis birefringent plates could: (i) generate larger FSR values, (ii) provide a smoother variation of modulation depth as the wavelength is tuned, (iii) enable faster tuning rates, and (iv) posses a larger range of usable filter rotation angles.…”
Section: Introductionmentioning
confidence: 99%